'It was my thought … he made it a reality': Normalization and responsibility in athletes' accounts of performance-enhancing drug use. (June 2013) - Pappa, Evdokia; Kennedy, Eileen
Despite the widespread interest in athletes' use of performance-enhancing drugs (PEDs) in track and field, the voices of the athletes who use banned substances have seldom been heard. Interviews with competitive athletes were conducted to explore their relationship to doping. Two themes emerged from the interviews. Firstly, the athletes presented doping as a normalized part of competitive sport, inevitably involving the participation of coaching staff. Secondly, and in contrast to the first theme, athletes maintained that they alone were responsible for the decision to use PEDs. The study supports the 'networked athlete' explanation of PED use, while highlighting the individualist explanation of doping offered by the athletes themselves. Foucault's concept of governmentality is used to explain this contradiction, by suggesting that athletes' internalization of responsibility for doping is part of the art of governing competitive sport.